Academic poster competition: A new approach in teaching and learning strategy for introduction to human development course - Ismail, Noraini; Abu Bakar, Nor Iman Nabila; Iswadi Efendi, Muhammad Danish Amin; Mohamad Razali, Muhammad Afis Firdaus (2022)
The COVID-19 pandemic forced all parties to optimize the use of online learning as a medium of teaching and learning. Different strategies have been implemented to improve learning outcomes. Therefore, academic poster competition was adopted into Human Development (CTU001) course as an effective mechanism in order to enhance the learning outcomes. As compared to the traditional method, students were only following the learning in classroom and complete written assignments but through the academic poster competition, students are given the opportunity to work in groups to produce posters as an added value to the knowledge gained during lecture sessions in class. It is more interactive, tests the mind, and can hone students' creativity. The findings of the study show that students are very positive about the implementation of the program and want it to continue again in the future. The implementation of the program has a positive effect on the improvement of students' knowledge and soft skills. Therefore, this program needs to be further developed with various methods in sustaining active learning to meet the challenges of 21st-century education.